HISTORY OF TASAWUF AND TAREKAT IN INDONESIA - Yulita Putri; Abid Nurhuda; Anastasia Anastasia; Ali Anhar Syi'bul Huda (International Journal of Integrated Science and Technology, 2023)
The tarekat is one of the main teachings in the field of Sufism where the two are interrelated and cannot be separated because they have a long journey and history since their inception until now. And the purpose of this study is to describe the history of thought in the field of tasawuf and tarekat in Indonesia. The method used is qualitative with a literature study approach when collecting data, then analyzed and concluded by verification. The results of the study show that the History of Thought in the Field of Sufism and Tarekat in Indonesia consists of four periods. Namely the first period, 1st and 2nd century H. second period, 3rd and 4th century H. third period, 5th century H. and fourth period, 6th century H and so on. The division of this period was strongly influenced by the differences and phenomena of the diversity of Islamic society and became the forerunner to the birth and emergence of tarekat in Islam which played an important role in realizing a moral-spiritual change in Indonesian society.